Liver ABCA1 Gene Expression in Male Rats: Effects of High-intensity Treadmill Running and Black Crataegus-pentaegyna (Siayh-Valik) Extraction - Abbass Ghanbari-Niaki; Monireh Gholizadeh; Safieyh Ghanbari-Abarghooi; Fatemeh Roudbari; Mohammad Javad Chaichi (The Society of Aging and Physical Activity (SAPA), 2014)
The purpose of the current study was to investigate the effect of a high- intensity treadmill running (8 weeks) with or without aqueous extraction of black Crataegus-Pentaegyna (Siyah -Valik) on liver ABCA1 mRNA expression and plasma HDL-C, total, and direct bilirubin concentration in male rats. Twenty Wistar male rats (4-6 weeks old, 140-170 g weight) were used. Animals were randomly assigned into training (n =10) and control (n =10) groups and further divided into saline-control (SC, n=5), saline-training (ST, n=5), black Crataegus-Pentaegyna (Siyah-Valik) Control (SVC, n=5), and black Crataegus-Pentaegyna (Siyah-Valik)-training (SVT, n=5) groups. Training groups have performed a high-intensity running program (34 m/min on 0% grade, 60 min/day and 5 days/week) on a motor-driven treadmill for 8 weeks. Animals were orally fed with black Crataegus-Pentaegyna (Siyah -Valik) extraction (500 mg/kg body weight) and saline solution for last six weeks. A significant differences have found in liver ABCA1 gene expression between SVC and SVT (P<0.003) and between SVC with SC groups (P< 0.038). HDL-C levels were significantly (P<0.036) between groups. A higher HDL level was found in SV treated groups and between SVC and SC groups. The levels of bilirubin total and bilirubin direct remained unchanged. The current results show that high-intensity treadmill running affected liver ABCA1 mRNA expression in different directions in saline (increase) and SV (decrease) treated animals. Findings also indicate an opposite pattern of change in saline and SV treated animals at rest. It seems the existence of opposite effect of exercise with supplementation of SV might be attributed to the suppression of lignds which is provided by SV supplementation at rest. This in turn might be also taking in account in lower liver ABCA1 mRNA expression and its related nuclear receptors such as LXR in SVT not ST groups.